Enhancement of NIR‐Absorbing Ability of Bis(diarylmethylium)‐Type Dicationic Dyes Based on an Ortho‐Substitution Strategy. Issue 23 (16th March 2023) - Harimoto, Takashi; Suzuki, Takanori; Ishigaki, Yusuke
Abstract: Electrochromic systems capable of switching near‐infrared (NIR) absorption are fascinating from the viewpoint of applications in the materials and life sciences. Although 11, 11, 12, 12‐tetraaryl‐9, 10‐anthraquinodimethanes (AQDs) with a folded form undergo one‐stage two‐electron oxidation to produce twisted dicationic dyes exhibiting NIR absorption, there is a need to establish a design strategy that can enhance the NIR‐absorbing abilities of the corresponding dicationic dyes. In this study, we designed and synthesized a series of AQD derivatives with various substituents introduced at the ortho ‐position(s) of the 4‐methoxyphenyl group. X‐ray and spectroscopic analyses revealed that NIR‐absorbing properties can be changed by introduction of the ortho ‐substituents. Thus, control of the steric and electronic effects of the ortho ‐substituents on the 4‐methoxyphenyl groups was demonstrated to be an effective strategy for fine‐tuning of the HOMO and LUMO levels for neutral AQDs and twisted dications, respectively, resulting in the modification of electrochemical and spectroscopic properties under an " ortho ‐substitution strategy". Abstract : An ortho ‐substitution strategy is key for controlling both steric and electronic effects of bis(diarylmethylium)‐type dicationic dyes. It was proven to be an effective strategy for fine‐tuning of their LUMO levels, resulting in the red‐shift and enhancement of NIR‐absorbing abilities (see picture).